Characteristics of natural wind - Pt. II: Turbulent flow - SHARAN, V. KR. (MAUSAM, 1975)
The characteristics of wind fluctuations are critically reviewed and analysed in terms of turbulence, intensiy, power spectral density and correlation coefficient, It is shown that root mean square gust speed decreases very slightly with height in the lower part of the boundary layer, Various mathematical models of power spectrum for the three components of the fluctuating wind velocity are critically discussed, It is noted that u and v spectra show a greater dependence on the type of the terrain suggesting that meso-scale features are of importance for the low frequency portion, The low frequency portion of u- and v-spectra react to changes in atmospheric stability with the v-spectrum being more dependent ~an u-spectrum, The u-spectrum follows the similarity theory the most of the three components, The vertical spectrum appears to be dependent on height whereas it is difficult to conjecture in favour of either hypothesis for the horizontal spectra, Correlation coefficient measurements of u-and v-components show that the length scales increase with height, Based on the assumption of Taylor's hypothesis and isotropy, expressions are given for the theoretical prediction of correlation coefficient, coherence and the various length scales. Both analytical and empirical gust factor models are presented and it is shown that the gust factor varies with the averaging time period, the site conditions and the height above the ground.